2016
DOI: 10.1080/03079457.2015.1129663
|View full text |Cite
|
Sign up to set email alerts
|

Variable protection against experimental broiler necrotic enteritis after immunization with the C-terminal fragment ofClostridium perfringensalpha-toxin and a non-toxic NetB variant

Abstract: Necrotic enteritis toxin B (NetB) is a pore-forming toxin produced by Clostridium perfringens and has been shown to play a key role in avian necrotic enteritis, a disease causing significant costs to the poultry production industry worldwide. The aim of this work was to determine whether immunization with a non-toxic variant of NetB (NetB W262A) and the C-terminal fragment of C. perfringens alpha-toxin (CPA247–370) would provide protection against experimental necrotic enteritis. Immunized birds with either an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Remarkably, immunization with NetB toxin, which is essential to cause disease in broilers, does not afford higher levels of protection than vaccination with other toxins or proteins. However, when birds were vaccinated either via the parenteral or the oral route, with a combination of both NetB toxin and alpha toxin, higher levels of protection were obtained [ 107 , 108 ]. In order to obtain full protection against C. perfringens -induced enteric diseases, not only antibodies that inhibit toxin activity might be needed; a combination of antigens targeting also bacterial proliferation, colonization and/or nutrient acquisition could be more efficient than either one of the individual approaches.…”
Section: Vaccination Strategies To Reduce Antibiotic Use For Diseasesmentioning
confidence: 99%
“…Remarkably, immunization with NetB toxin, which is essential to cause disease in broilers, does not afford higher levels of protection than vaccination with other toxins or proteins. However, when birds were vaccinated either via the parenteral or the oral route, with a combination of both NetB toxin and alpha toxin, higher levels of protection were obtained [ 107 , 108 ]. In order to obtain full protection against C. perfringens -induced enteric diseases, not only antibodies that inhibit toxin activity might be needed; a combination of antigens targeting also bacterial proliferation, colonization and/or nutrient acquisition could be more efficient than either one of the individual approaches.…”
Section: Vaccination Strategies To Reduce Antibiotic Use For Diseasesmentioning
confidence: 99%
“…There are some evidences that the Tpel have little effect on pathogenesis of NE and induces partial protection against NE [7,8]. However, there is no consensus in this regard and some researchers believe that it increases virulence of C. perfringens while others found no evidence of involving Tpel in the NE pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that immunizing ability for protection against NE was associated with several virulence factors. The most important of these virulence factors are phospholipase C known as Alpha-toxin, β-pore forming toxin, NetB, and a zinc metallopeptidase protein [7,8,28]. Utilizing a fusion of non toxic variants of these proteins as a recombinant subunit vaccine candidate could enhance protective immunity [31,6].…”
Section: Introductionmentioning
confidence: 99%
“…PE is the most abundant phospholipid present in intestinal epithelial cells (39) and is therefore a probable nutrient source during lesion formation at the intestinal mucosa, where C. perfringens cells are present in high numbers. PE can also be hydrolyzed by CPA (40), a zinc metallophospholipase C that, although no longer considered to be the key toxin involved (41), still appears to play a role in NE pathogenesis (42)(43)(44). Ethanolamine has been specifically implicated in virulence, due to its ability to serve as a sole carbon and nitrogen source for some bacterial pathogens, including C. perfringens (45).…”
Section: Discussionmentioning
confidence: 99%